Overlapping anthropogenic effects on hydrologic and seasonal trends in DOC in a surface water dependent water utility. (1st January 2019) - Parr, Thomas B.; Inamdar, Shreeram P.; Miller, Matthew J.
Abstract: Drinking water supplies are increasingly affected by overlapping anthropogenic global change processes. As a key currency of ecosystem function in aquatic ecosystems, dissolved organic carbon (DOC) concentration and composition is sensitive to many global change processes. However, DOC must also be removed to avoid the production of harmful disinfection byproducts as water is processed. Thus, understanding the effects of global change processes on the seasonal and long-term dynamics of DOC composition and concentration is critical for ensuring the sustainability of drinking water supplies. To understand these dynamics, we analyzed a novel 11-year time series of stream water DOC concentration and composition using Weighted Regressions on Time Discharge and Season (WRTDS) to understand the influences of co-occurring changes in climate and atmospheric deposition. We also discuss the implications for water supply provision and management. We found that, during our study period, overlapping global change processes in the watershed had the net effect of increasing the DOC aromaticity, as measured by SUVA254, at moderate to high discharge levels during the late spring and early summer and the autumn and early winter. However, changes in DOC concentration were more dynamic and we observed both increasing and decreasing trends depending on season and hydrologic state. During summer, at low to moderate flow levels we observed a significant (p < 0.05) increase in DOC concentration. During autumn, at moderate to high flow levels we observed a significant (p < 0.05) decrease in DOC concentration and an increase in SUVA254 . For drinking water providers, our results suggest that close monitoring of source waters must be coupled with the development of plans accounting for season- and hydrology-specific long-term changes. Graphical abstract: Highlights: Direction of DOC concentration change was seasonally and hydrologically divergent. Changes in DOC composition were partly asynchronous with changes in concentration. Trends in anthropogenic inputs and climate likely explain patterns of change in DOC. Sustainable water supply requires hydrologic and seasonal understanding of DOC trends.